Characterization of the nearly complete mitochondrial genome of ochraceous darkies, Euphaea ochracea Selys, 1859 (Odonata: Zygoptera: Euphaeidae) and phylogenetic analysis - Marylin Miga, Marylin Miga; Jahari, Puteri Nur Syahzanani; Sivachandran Parimannan, Sivachandran Parimannan; Heera Rajandasb, Heera Rajandasb; Latif, Muhammad Abu Bakar; Yap Jing Wei, Yap Jing Wei; Shamsir, Mohd Shahir; Mohd Salleh, Faezah (Taylor&francis, 2023)
In the present study, the nearly complete mitochondrial genome of Euphaea ochracea was described and its phylogenetic position in the family Euphaeidae was analyzed. Here, we recovered 13 proteincoding genes, 22 transfer RNAs, 2 ribosomal RNAs and a partial control region, resulting in a mitogenome length of 15,545bp. All protein-coding genes were initiated by the typical ATN codon except nad3 and nad1, which utilizes the TTG codon. Four protein-coding genes (cox1, cox2, cox3 and nad5) are terminated by an incomplete stop codon T, while others end with either a TAA or TAG codon. The intergenic spacer region, S5, is absent in this mitogenome, supporting the lack of this region as a specific character in damselflies. Phylogenetic analysis showed that the newly sequenced E. ochracea is phylogenetically closer to E. ornata with a high support value.